I, Maya Plisetskaya - Pliset͡skai͡a, Maĭi͡a, 1925-2015. (New Haven ; London : Yale University Press, 2001)
Maya Plisetskaya rose to become a prima ballerina of Moscow's Bolshoi Ballet after an early life filled with tragedy. Here Plisetskaya reflects on her personal and professional odyssey presenting the life of a Soviet artist from the 1930s to 1990s.
The dacha and Sretenka Street -- What I was like at five -- Relatives -- Spitzbergen -- I study ballet -- Back in school and father's arrest -- My mother disappears -- Chimkent -- Concert for the Cheka -- Tchaikovsky's ʼImpromptuʼ -- The war -- My first year at the Bolshoi Theater -- The apartment on Shchepkinsky Passage -- Mastering the ABCs of the theater -- ʼRaymondaʼ -- ʼSwan Lakeʼ -- Youth festivals -- My injuries, my healers -- Who'll get whom! -- Stalin's birthday -- I dance in ʼDon Quixoteʼ -- I dance in Golovanov's opera -- Life on the road and the end of the Stalinist era -- My trip to India -- Persecution -- How I didn't go to London -- While the company was in London -- How I dressed -- What a person needs -- Shchedrin -- Life on Kutuzovsky Prospect -- I go to America -- Seventy-three days -- How we were paid -- Paris meetings -- Work with Yakobson -- Why I did not stay in the West -- Marc Chagall draws me -- November 20 -- How ʼCarmen Suiteʼ was born -- Work with Roland Petit and Maurice Bjart -- A lyrical digression -- My ballets -- My ballets (continued) -- I want justice -- Work in Italy -- Work in Spain -- Untitled -- Years of wandering -- Curfew.
Translated from the Russian.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Pliset͡skai͡a, Maĭi͡a, -- 1925-2015.; Pliset͡skai͡a, Maĭi͡a, -- 1925-2015; Ballerinas -- Soviet Union -- Biography; Ballerines -- URSS -- Biographies; MUSIC -- General; Ballerinas; Soviet Union; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies